2017
DOI: 10.1002/2016wr019393
|View full text |Cite
|
Sign up to set email alerts
|

Tracer‐based characterization of hyporheic exchange and benthic biolayers in streams

Abstract: Shallow benthic biolayers at the top of the streambed are believed to be places of enhanced biogeochemical turnover within the hyporheic zone. They can be investigated by reactive stream tracer tests with tracer recordings in the streambed and in the stream channel. Common in‐stream measurements of such reactive tracers cannot localize where the processing primarily takes place, whereas isolated vertical depth profiles of solutes within the hyporheic zone are usually not representative of the entire stream. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 60 publications
8
99
1
Order By: Relevance
“… Difficult Run: (a) site map with surface (blue dots) and hyporheic (red dots) sampling sites identified (modified with permission from Knapp et al . []) and (b) longitudinal profile. Note that the stream width in Figure a is not to scale.…”
Section: Methodsmentioning
confidence: 99%
“… Difficult Run: (a) site map with surface (blue dots) and hyporheic (red dots) sampling sites identified (modified with permission from Knapp et al . []) and (b) longitudinal profile. Note that the stream width in Figure a is not to scale.…”
Section: Methodsmentioning
confidence: 99%
“…For the STS-HTS model, the calibration was performed with respect to the TS ratio (f s ), exchange rate between the stream and TS, (α s ), the exchange rate between the stream and stream bed (α b ), and the stream-bed decay and transformation rate coefficients (k b1 , k b12 and k b2 ). The MITS and the STS decay and transformation rate coefficient values for the stream were adopted from [12] [32], because most of the microorganisms were found in this layer, and the estimated penetration of the tracer diffusion front into the HTS during the experiment did not exceed 0.01 m. Note that Knapp et al [33] concluded that the benthic biolayer was found to be on average 2 cm thick, ranging from one third to one half of the full depth of the hyporheic zone. Two sets of calibrations were performed with the STS-HTS model.…”
Section: Model Calibrationmentioning
confidence: 99%
“…Longitudinal patterns converged in ND‐LEEF streams later in the colonisation sequence (after day 87), suggesting that biofilm growth clogged interstitial spaces over time and homogenised the effect of substrate (Aubeneau et al., ; Hanrahan et al., ). Previous studies have noted that raz transformation is highest in near subsurface compartments of the benthic biolayer (Knapp et al., ), representing the “micro”‐hyporheic zone (Shogren et al., ), where microorganisms are most abundant (sensu Battin, Besemer, Bengtsson, Romani, & Packmann, ). As such, changes in the exchange rate of water and dissolved constituents between surface and subsurface zones would be reflected in raz transformation rates.…”
Section: Discussionmentioning
confidence: 99%